Cover Feature: An Interfacial Study of Au(111) Electrodes in Deep Eutectic Solvents (ChemElectroChem 14/2022). Issue 14 (22nd June 2022) - Zeller, Sven J.; Geng, Tanja; Ceblin, Maximilian U.; Uhl, Matthias; Kuehne, Alexander J. C.; Kibler, Ludwig A.; Jacob, Timo
Abstract : The Cover Feature illustrates the interface between an Au(111) single crystal electrode surface with deep eutectic solvents (DES) of different types and composition. The different systems were studied with cyclic voltammetry as well as electrochemical impedance spectroscopy, revealing important and interesting new insights into the electrode/electrolyte‐interfaces. More information can be found in the Research Article by S. J. Zeller et al .